Efektivitas Hukum Alat Bukti Elektronik Dalam Pemeriksaan Bukti Di Pengadilan Tata Usaha Negara - Asaad, Annisa Febriana (Universitas Semarang, 2023)
This study aims to analyze the legal effectiveness of electronic evidence in examining evidence at the Makassar City State Administrative Court and to analyze the obstacles faced by the Makassar City State Administrative Court in examining electronic evidence. Electronic Evidence is a form of implementing the digitalization era which is then expected to be able to keep up with the times. The application of electronic information in the judicial environment is considered capable of realizing the vision and mission of the Supreme Court as an Indonesian judicial institution. The urgency of applying electronic evidence in the judicial process in Indonesia is of course to determine its effectiveness both from the point of view of all process organizers and applicable rules. The research method used is empirical research method.The results of the study concluded that the examination of electronic evidence at the State Administrative Court was not optimal. This is caused by several things, namely, there are no legal regulations that specifically regulate procedural proving of electronic evidence, the unavailability of institutions that can help determine the authentication of evidence at low cost, and the non-fulfillment of existing legal effectiveness factors. as; legal factors; law enforcement factor; and facilities and infrastructure factors. Penelitian ini bertujuan untuk menganalisis efektivitas hukum alat bukti elektronik dalam pemeriksaan bukti di Pengadilan Tata Usaha Negara Kota Makassar dan menganalisis kendala yang dihadapi oleh Pengadilan Tata Usaha Negara Kota Makassar dalam pemeriksaan alat bukti elektronik. Bukti Elektronik merupakan wujud implementasi era digitalisasi yang kemudian diharapkan mampu mengikuti perkembangan zaman. Penerapan informasi elektronik di lingkungan peradilan dinilai mampu mewujudkan visi dan misi Mahkamah Agung sebagai lembaga peradilan Indonesia. Urgensi penerapan alat bukti elektronik dalam proses peradilan di Indonesia tentunya untuk mengetahui keefektifannya baik dari segi semua penyelenggara proses maupun aturan yang berlaku. Adapun metode penelitian yang digunakan ialah metode penelitian empiris. Hasil penelitian disimpulkan bahwa pemeriksaan alat bukti elektronik di Pengadilan Tata Usaha Negara belum optimal. Hal ini disebabkan oleh beberapa hal, yaitu, belum ada aturan hukum yang mengatur secara khusus terkait prosedural pembuktian alat bukti elektronik, tidak tersedianya Lembaga yang dapat membantu menentukan autentikasi dari alat bukti dengan biaya yang murah, serta tidak terpenuhinya faktor-faktor efektivitas hukum yang ada seperti; faktor hukum; faktor penegekan hukum; dan faktor sarana dan prasana.